Quality retention of microwave dried pineapple core and peels - Ismail, Siti Fabilah (2017)
The purpose of this research is to study the effect of microwave power on the drying characteristics of pineapple peels and core. This research is also done to evaluate the total phenolic content and antioxidant activity in fresh and dried pineapple peels and core. The pineapple peels and core were dried under different microwave power (180 W, 450 W and 850 W). After that, both peels and core of fresh and dried were extracted at 50 °C for 30 minutes using ethanol solution. The extract samples were used for analysis of total phenolic content and antioxidant activity (DPPH Assay). The results showed higher microwave power led to shorter drying time, thus resulting to high drying rate. Drying kinetic for microwave showed three drying periods, i.e. i) heating period, ii) constant drying rate period and iii) falling rate period. On the other hand, dried peels and core resulted in high total phenolic content compared to fresh ones. Dried peels and core exhibited 19.8 mg GAE/ g dry sample and 21.3 mg GAE/ g dry sample, respectively at microwave power of 180 W and 850 W. Furthermore, dried peels and core were also found to be potentially scavenged radical molecules. Dried core at 180 W revealed to be a good extraction to scavenge free radical as it was achieved around 74 % of DPPH inhibition. From forgoing results, microwave drying can be a good process to be practiced in food preservation as it helps improved the quality of product.